Transcarpathian Petroleum Province in Romania (Geo-Eco-Marina, 2021)
The Transcarpathian Zone, a modest hydrocarbon province so far, is part of the Inner Carpathians and is shared across northern Romania, Ukraineand Slovakia. Iňačovce-Kričevo, Pieniny and Magura nappes emplacement over the Dacia Mega-Unit’s, Petrova and Botiza sedimentary covers started inthe Oligocene and finalized during the Burdigalian collision of ALCAPA and Tisza-Dacia mega-units, now separated by the Bogdan-Dragos Vodă Fault. Thenappe emplacement triggered the Oligocene source rocks maturation, expulsion-migration and accumulation of hydrocarbons. A broad review of structuraland lithostratigraphic framework of Petrova and Botiza foreland basins is integrated in the description of oil habitat of this province. The oil bearing Petrovaforeland is narrow and less extended than the oil-prone Botiza foreland. In the latter foreland, Oligocene-early Miocene backbulge, forebulge and foredeepdepozones were first recognised and characterised. The foreland basins fill consists of late Cretaceous – early Miocene successions which include clasticreservoirs and Maikopian bituminous source rocks belonging to two independent thermogenic petroleum subsystems. The unconformable mid-Miocene-Quaternary Megasequence of the Transcarpathian pull-apart basin is the post kinematic cover of the Transcarpathian Zone. It bears a thermogenic (andlocally, a biogenic) gas petroleum system that extends up to the East Slovakia Bassin. The main purpose of this paper is to detail the basin forming and fillof the area and to evaluate of the petroleum systems, previous exploration work and to asses resulting resources.
Keywords: Transcarpathian Zone and Basin; Pieniny Klippen Belt; Magura Units; forelands lithostratigraphy; petroleum systems; resources; oil and gas accumulations; history of exploration